2016
DOI: 10.1051/0004-6361/201527271
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional time evolution of beam-plasma instability in the presence of binary collisions

Abstract: Energetic electrons produced during solar flares are known to be responsible for generating solar type III radio bursts. The radio emission is a byproduct of Langmuir wave generation via beam-plasma interaction and nonlinear wave-wave and wave-particle interaction processes. In addition to type III radio bursts, electrons traveling downwards toward the chromosphere lead to the hard X-ray emission via electron-ion collisions. Recently, the role of Langmuir waves on the X-ray-producing electrons has been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 59 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…2016; Tigik et al. 2016), where collisions are usually introduced by means of a collisional operator at the right-hand side of the Vlasov equation. The choice of the proper collisional operator remains an open problem.…”
Section: Solar Wind Heating: a Huge Problemmentioning
confidence: 99%
“…2016; Tigik et al. 2016), where collisions are usually introduced by means of a collisional operator at the right-hand side of the Vlasov equation. The choice of the proper collisional operator remains an open problem.…”
Section: Solar Wind Heating: a Huge Problemmentioning
confidence: 99%
“…Understanding these evolutions requires advanced theories and multi-scale modeling to combine exospheric mechanisms involving suprathermal electrons (e.g., velocity filtration), and effects of solar wind expansion (e.g., magnetic focusing and increase of parallel temperature) with diffusion in pitch angle and energy induced by collisions (at low distances in the outer corona) and by wave-particle interactions (Zouganelis et al 2005;Tigik et al 2016;Innocenti et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this simplifies the models and is grounded by observations of electrons with small pitch angles at 1 AU, it is still a major simplification. Recent efforts have been undertaken (Ziebell et al, 2014(Ziebell et al, , 2015(Ziebell et al, , 2016Tigik et al, 2016) to model the plasma emission process in two velocity dimensions for a single point in space, taking into account all the steps involved in the plasma emission process. In the simulations by Ziebell et al (2015), fundamental emission was generated by Langmuir waves both with ionsound waves and by scattering.…”
Section: Electron Beam Propagationmentioning
confidence: 99%
“…These processes dominated initially, whilst over time the harmonic emission overtook the fundamental. Taking into account collisions, Tigik et al (2016) found that a wider plateau was formed in the distribution function and increased the tendency to isotropization.…”
Section: Electron Beam Propagationmentioning
confidence: 99%